2003
DOI: 10.1074/jbc.m305851200
|View full text |Cite
|
Sign up to set email alerts
|

MAHRP-1, a Novel Plasmodium falciparum Histidine-rich Protein, Binds Ferriprotoporphyrin IX and Localizes to the Maurer's Clefts

Abstract: Using a stage-specific cDNA library from Plasmodium falciparum we have identified a gene coding for a novel histidine-rich protein (MAHRP-1). The gene is exclusively transcribed during early erythrocyte stages and codes for a small transmembrane protein. The C-terminal region contains a polymorphic stretch of histidine-rich repeats. Fluorescence microscopy studies using polyclonal mouse sera revealed that MAHRP-1 is located at the Maurer's clefts, which represent parasite-induced structures within the cytosol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 51 publications
(90 reference statements)
5
101
0
1
Order By: Relevance
“…However, there are exceptions to the rule that a PEXEL/VTS motif is needed to cross the PVM, because some PEXELnegative exported proteins have been documented (Blisnick et al, 2000;Spycher et al, 2003). Our analysis of the cluster of ring stage-specific genes on chromosome 9 revealed that only two of the 4 exported proteins possess an obvious PEXEL.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, there are exceptions to the rule that a PEXEL/VTS motif is needed to cross the PVM, because some PEXELnegative exported proteins have been documented (Blisnick et al, 2000;Spycher et al, 2003). Our analysis of the cluster of ring stage-specific genes on chromosome 9 revealed that only two of the 4 exported proteins possess an obvious PEXEL.…”
Section: Discussionmentioning
confidence: 97%
“…The remaining five genes code for PEXEL-negative proteins. The locations of three of these (now called SBP1, MAHRP1, and REX2) have since been determined, and they are all exported to the Maurer's clefts (Blisnick et al, 2000;Spycher et al, 2003;this study). Hence, apart from the ETRAMPs (which are exported but do not need a PEXEL, because they remain in the PVM), Ͼ50% of the identified proteins do not have a PEXEL, and all three tested so far are exported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one gene was up-regulated by at least threefold in all five selections: PF14_0472, a member of the Plasmodium helical interspersed subtelomeric (PHISTa) family (37). Six other up-regulated genes encode proteins predicted or proven to be exported: P. falciparum erythrocyte membrane protein 3 (PfEMP3) (38), ring-IE surface antigen (RESA-1) (39), membrane associated histine-rich protein 1 (MAHRP-1) (40), and three others with a Pexel motif: PF14_0740, PF11_0035, and PFF0055w (37). These six genes and PF14_0472 are up-regulated at time point 3 (16-24 h postinvasion) in almost all selections, indicating that they could be translated in time for cytoadherence at the pigmented trophozoite stage.…”
Section: Some Exported Proteins Show Increased Transcription In Hbec-mentioning
confidence: 99%
“…The HRPs (histidine-rich proteins) of P. falciparum (PfHRP II, III, IV and membraneassociated histidine-rich protein-1 etc. ), which readily bind multiple haem monomers [10][11][12], have been suggested to play a crucial role in the haem detoxification process. These HRPs may also be involved in the neutralization of toxic haem in the parasite cytoplasm and infected red blood cells by removing haem that is membrane bound [13].…”
Section: Introductionmentioning
confidence: 99%